Company Law - Painter, Desmond. author. aut Link
XI, 204 p.
Keywords: A set of twenty problems in company law. The loose-leaf case study pages are licensed for bona fide lecturers to photocopy for assignment and seminar use. Full lecturers notes are provided showing how the cases can be fully updated in practical, activity-based study.